INOVASI KEPEMIMPINAN KEPALA MADRASAH SEBAGAI UPAYA PENINGKATAN KUALITAS PENDIDIKAN DI MTS PERSIS 37 SUMEDANG - Sariah, Dedeh; Mulyawan Safwandy Nugraha; Shamsuddin MST (STAI Ma'had Aly Al-Hikam Malang, 2024)
The head of the madrasah as an education leader needs to have innovation and creative ideas to improve the quality of education. Innovative and creative leaders are very important to create madrasahs that are in demand by the community and education stakeholders, increase competitiveness and be able to answer the challenges of the times. This study aims to describe the leadership innovations of madrasah heads and the efforts of madrasah heads in improving the quality of education in MTs Persis 37 Sumedang. The method used in this study is qualitative with interview data collection techniques, observation and document analysis. The results of this study show that the leadership innovation of madrasah heads at MTs Persis 37 Sumedang conducted through several programs and activities such as adab-based curriculum, literacy activities, reading the Qur'an, reading books, writing verses of the Qur’an, summarizing books and featured programs, namely